Attachment Capability of Antagonistic Yeast Rhodotorula glutinis to Botrytis cinerea Contributes to Biocontrol Efficacy - Li, Boqiang; Peng, Huaimin; Tian, Shiping (Frontiers in Microbiology, 2016)
Rhodotorula glutinis as an antagonism show good biocontrol performance against various postharvest diseases in fruits. In the present study, strong attachment capability of R. glutinis to spores and hyphae of Botrytis cinerea was observed. Further analysis showed that certain protein components on the yeast cell surface played critical role during the interaction between R. glutinis and B. cinerea. The components mainly distributed at the poles of yeast cells and might contain glycosylation modification, as tunicamycin treated yeast cells lost attachment capability to B. cinerea. To investigate contributions of attachment capability of R. glutinis to its biocontrol efficacy, yeast cells were mutagenized with 3% methane-sulfonic acid ethyl ester (EMS), and a mutant CE4 with stable non-attaching phenotype was obtained. No significant difference was found on colony, cell morphology, reproductive ability and capsule formation between the mutant and wild type. However, there was a distinct difference in India ink positive staining patterns between the two strains. Moreover, wild type strain of R. glutinis showed better performance on inhibiting spore germination and mycelial growth of B. cinerea than CE4 strain when yeast cells and B. cinerea were co-cultured in vitro. In biocontrol assay, both wild type and CE4 strains showed significant biocontrol efficacy against gray mould caused by B. cinerea in apple fruit, whereas, control effect of CE4 strain was lower than that of wild type. Our findings provided new evidences that attachment capability of R. glutinis to B. cinerea contributed to its biocontrol efficacy.